(3QSGdI aj GdQVGYs - (3GdcQcj GdYGedj, CHh GdMSf, GdeMbb GdKGfj, GdeMbb GdKGfj, Ydj Hf GdMSjf Hf YHO GdYGdj GdcQcj GdYGedj, J (B940(3g` (B1534(3es ((3cQHdGAs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg ceG gh Cgdg(B... (3habc Gddg Efg bO GTJgQ Ydi CdSfI GdWdHI aj gPG GdYUQ JMQje GdeQCI Ydi HYdgG HEQVGY ef SfPcQg hdG fYQa dge aj PGc GUdGs
(3BNQgG (B:s
(3BNQgG(B: (3hdjS HKGHJ Hd fefY GdJdGRe CUdG aEf KHhJ HfhI TNU dBNQ jbJVj KHhJ GdCNhI dChdGOg dG KHhJ GdCNhI dCNhI ChdGOg hPdc ZjQ ebJVj ddJMQje HhLg ef GdhLhgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L(B4: 281s
(3GdPQjYI, L (B11: 138 - 139s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis